Management of Character Education in Creating Student Morals: A Multiple-Case Study - Fanani, Zainuddin; Basri; Sonhadji, Ahmad (Jurnal Pendidikan Islam, 2022)
Purpose – Quality education with Islamic values will result from character education with good management. This study analyzes and plans character education in MAN 1 Malang Regency and MAN 1 Malang City while implementing and evaluating character education in these institutions. This study also looks at the role of character education in MAN 1 Malang Regency and MAN 1 Malang City. Design/methods/approach – This research uses case studies and multi-case designs. In-depth interviews, participant observation, and documentation were used to collect data. To conclude, the data are presented in an interactive model. The data’s trustworthiness, transferability, dependence, and certainty were tested for validity. Analyze data with reflective thinking. Findings – The findings of this study indicate that character education is planned using a curriculum that includes character education. Character education with good habits, role models, extracurricular activities, and fostering the organizational culture of character education, regular meetings, and home visits to assess the impact of character education on students’ morale by producing character education management. Based on the previous year’s evaluation, designing academic and non-academic curricula, managing the extracurricular environment, and creating a religious culture. Madrasa environment, teaching and learning activities, and extracurricular activities. The head of the madrasah conducts evaluation activities gradually, periodically, and continuously involving the waka and related fields and learning from the vision and mission of the madrasa, creating moral habituation, environmental protection, and cooperation with all stakeholders. Research implications/limitations – The study highlights the significance of merging character education with Islamic values in two Islamic schools through good habits, role models, extracurricular activities, and organizational culture while stressing the importance of regular evaluations and collaboration among stakeholders. However, the research’s qualitative methods and limited scope may not be generalizable to all Islamic educational institutions. Practical implications – Integrating character education in curricula, emphasizing good habits and extracurricular activities, continuous evaluations, and stakeholder collaboration can effectively promote Islamic values in educational institutions.